PENERAPAN KUOTA PEKERJA BAGI PENYANDANG DISABILITAS PADA BUMN DAN BUMD DI DKI JAKARTA - Hidayatullah, Fajri (Asosiasi Pengajar Hukum Tata Negara dan Hukum Administrasi Negara (APHTN-HAN) Sumatera Utara, 2022)
Policies and regulations related to legal protection for persons with disabilities in Indonesia are adequate, but overall they have not been implemented optimally. The results of the research at FHCI as a partner invited by BUMN and BUMD, have not employed persons with disabilities in accordance with existing regulatory provisions and have not carried out their obligations by providing fulfillment of the rights of disabled workers as regulated in Law Number 13 of 2003 concerning Manpower. The purpose of this study is to knowing and analisys for implementation regarding the policy of recruiting disabled workers in BUMN and BUMD, while the research method used is descriptive qualitative, which is a data analysis method that is carried out by processing and analyzing systematically, the results of the study show that the implementor has not implemented the regulatory provisions. that already exists, so that the reality that occurs in the recruitment of disabled workers has not run optimally, in terms of recruitment and placement, as well as not fulfilling the quota that has been determined for disability in BUMN and BUMD. FHCI, BUMN and BUMD have not fulfilled the rights of persons with disabilities in terms of providing job opportunities, providing skills training and getting decent jobs without discrimination. Based on the background described, this research focuses on “Implementation of work quotas for persons with disabilities”.